New ways of inhabiting the city: Aerotropolis and Generic City. The case of Quito - Rosero Añazco, Verónica (Estoa. Journal of the Faculty of Architecture and Urbanism, 2015)
Is the contemporary city like the contemporary airport- “all the same”? This hypothesis in "The Generic City" (Koolhaas, 1997) is even more controversial with the following scenario: what happens when a territory is planned based on an airport, a "non-place", as qualified by Marc Augé? (Augé, 1993) The "aerotropolis" is an urban model that has been applied in various cities around the world in general terms, despite the obvious differences that may exist in cultural, geographical, economic, idiosyncratic, and sociopolitical aspects. John Kasarda, author of the concept of aerotropolis (Kasarda, 2000), argues that although their basic planning principles can be applied to most places, the successful implementation of an aerotropolis relies strongly on local factors. Can the airport and its affected territory reach a symbiotic integration, where the first one contributes with an economic capital and the second one with the identity? Through the case of the New Quito International Airport, we reflect on this dispute through a critical analysis of its territory. Strategies like the contrast with the Greek polis, or the approach to intelligent territories, provide lights to the debate on this new form of living and planning the city. Keywords: aerotropolis, generic city, Quito, smart territory.